Improving Motivation to Learn Hajj, Zakat and Waqf Material Using Problem Based Learning Model at State Vocational School 1 Lubuk Basung - Putra, Telma (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve the learning of hajj, zakat and waqf and morality in Islamic religious education learning using problem based learning. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were vocational high school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that problem based learning can improve Islamic education about learning of hajj, zakat and waqf and morality in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 48.78%, the first cycle 54.81% and in the second cycle it increased to 51.59%. Thus, the use of problem based learning model can be used as an alternative to improve student learning outcomes in Islamic religious education learning.